Insight into the mechanism of decreasing N-nitrosodimethylamine by Lactobacillus pentosus R3 in a model system. (March 2021) - Shao, Xuefei; Xu, Baocai; Zhou, Hui; Chen, Conggui; Li, Peijun
Abstract: The mechanism of decreasing N- nitrosodimethylamine (NDMA) by Lactobacillus pentosus R3 isolated from Chinese dry sausage was assessed in a model system. The model system was devised using a DeMan-Rogosa and Sharp-ferrous sulfate broth supplement with NDMA or its precursors. The results showed that inoculating L. pentosus R3 could significantly decrease the content of NDMA ( P  < 0.05). The NDMA precursors (dimethylamine and putrescine) were found to be decreased by L. pentosus R3 ( P  < 0.05). Nitrite was degraded to nitrosonium cation by acidolysis, which may promote the formation of NDMA. Direct degradation of NDMA by L. pentosus R3 was also observed. The strain exhibited antioxidant activities, including Fe 2+ chelating activity, which may be responsible for inhibiting the formation reaction and decreasing the precursors of NDMA. Thus, L. pentosus R3 decreased the content of NDMA possibly by three ways: inhibition of the formation reaction, decrease in precursors (DMA and putrescine) and direct degradation. It is interesting to understand the mechanism of decreasing NDMA by L. pentosus R3 to improve the safety of fermented meat products. Highlights: The Lactobacillus pentosus inoculation directly degraded N- nitrosodimethylamine. The L. pentosus inoculation decreased the contents of putrescine and dimethylamine. The L. pentosus inoculation inhibited the N- nitrosodimethylamine formation reaction. The antioxidation of L. pentosus contributed to the N- nitrosodimethylamine decrease.